What Have We Learned from the Economics of the Family - Willis, Robert J. (American Economic Review, 1987)
The family is distinguished from other social institutions, such as firms, by its crucial role in the production and nurture of children and its rationale is ultimately to be found in the preferences of individuals for own children. Sexual reproduction means that the production of one's own child requires the participation of another person of the opposite sex. The production of a child who will survive, become a successful adult, and produce his or her own children requires the expenditure of both personal and purchased resources over a lengthy period of time. Although interesting insights on the family can be culled from the classics, systematic development of the economics of the family is a recent phenomenon, beginning in the late 1950's when Harvey Leibenstein (1957) and Gary Becker (1960) attempted to address the determinants of fertility behavior within the framework of consumer theory. In this paper, I provide a brief overview of the history of family economics since 1960 and, along the way, offer a selective assessment of what has been learned from it. I attempt this assessment by asking how far we have progressed in answering a few of the larger theoretical, empirical, and policy questions that have motivated economists' interests in an area customarily studied by sociologists and demographers, or that have caused economists dealing with more traditional subject matter to incorporate the family into their work. Among the set of questions that have been addressed within the literature during the past twenty-five years are: 1) What are the causes of the historical association between economic growth and development and demographic transition from high to low levels of fertility and mortality? Of what relevance is the historical experience of currently developed countries to contemporary LDCs? Should fertility reduction be a primary goal of policy in the developing countries? Are the developed countries in danger of extinction because of fertility below replacement levels? 2) What was the cause of the post-World War II and subsequent bust? Was the baby boom a one-time aberration from a secular decline in fertility, or can we expect substantial fluctuations in the birth rate in the future? What are the consequences of the baby boom for the economic welfare of cohorts born during and after the boom? 3) Is the traditional family dead in the United States and other developed countries? Why did the divorce rate double in a decade? Why the growth in female-headed households? Why do so many divorced fathers fail to support their children? Has the sexual division of labor within the family changed as a consequence of the growth of female labor supply? To what extent are these changes in the family caused by social policy, and to what extent are they a product of basic market forces associated with modern economic development? What are the consequences of these changes for the welfare of future generations? I attempt to touch on some issues from each of the three areas in which the questions are grouped. However, constraints imposed by limitations of space, time, and most imtDiscussants: Kenneth Wolpin, Ohio State University; Robert Pollak, University of Pennsylvania; T. Paul Schultz, Yale University.